Case studies on functional testing techniques for software systems - Ong, Si Han. (2010)
Many surveys show that the cost and effort spent on software testing is more than 40% of total software development cost and effort respectively. The analysis of software code plays an important role in the testing. It is not possible to build a quality software product without good testing and analysis. The use of toolkits is a key to the quality of software testing and analysis. This project investigates Software Testing techniques, in particular the 3 methods of Black Box Testing, namely the equivalence class partitioning, the Boundary Value Analysis and Cause Effect Testing in depth. The project will subject methods from the Java Programming Language Application Programming Interfaces to manual testing using the Black Box Techniques.